PERSEPSI MASYARAKAT TERHADAP KUALITAS PELAYANAN PUBLIK PADA LAYANAN BEGITU DICETAK KTP KIA DIANTAR (BECAK PINTAR) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN GROBOGAN TAHUN 2025 - Valentino Volta Fernando; Neny Marlina (Journal of Politic and Government Studies, 2026)
Public service is a government function to meet the needs of the community, including population administration services. The Department of Population and Civil Registration (Disdukcapil) of Grobogan Regency provides the Smart Rickshaw service (Once Printed, KTP/KIA Delivered) to make it easier for the public to manage population documents online. This study aims to analyze the community's perception of public service quality in the Smart Rickshaw service. The study uses a descriptive quantitative method with a SERVQUAL approach that includes the dimensions of Reliability, Responsiveness, Assurance, Tangible, and Empathy. The research sample consisted of 100 respondents, determined using Slovin's formula from a population of 7,582 service users in 2025. Data were collected through questionnaires and analyzed using descriptive statistics. The results showed that the quality of public service in the Smart Rickshaw service falls into the good category with an overall average score of 3.58. The Reliability dimension scored the highest (3.67), while Tangible scored the lowest (3.44). The highest indicator was fair service provided without discriminating against service users, with an average score of 4.12, while the lowest indicator was the clarity and ease of understanding of the digital service display, with an average score of 2.89. These findings show that Becak Pintar services make it easier to handle population administration, but improvements are needed in the digital service display to make service quality even better.